Nurses and Unlicensed Assistive Personnel's Practices in Caring for Patients With Delirium in Acute Care Settings: Protocol for the PRACTICE Study - Mailhot, Tanya; Crump, Laura; Leblanc, Marie-Eve; Sanzone, Lia; Alfonso, Linda Victoria; Laughrea, Elisabeth; Oliver, Catherine; Bitzas, Vasiliki; Clausen, Christina; Lavoie, Patrick (Science of Nursing and Health Practices / Science infirmière et pratiques en santé)

(untitled) (Réseau de recherche en interventions en sciences infirmières du Québec (RRISIQ), 2023)
Introduction: Few studies have investigated nursing practice in relation to delirium in acute care settings, and no studies have investigated the care of unlicensed assistive personnel (UAPs) in this context. As a result, it becomes challenging to support the delivery of optimal care and thereby improve delirium-related patient outcomes.Objective: This manuscript reports on the development of two survey tools and a study protocol that aims to (1) describe the current practices of nurses and UAPs in the context of nursing care in delirium and to (2) highlight the barriers and facilitators to the delivery of optimal delirium care.Methods: This multi-method study aims to recruit nurses and UAPs. During an initial quantitative phase, participants will answer two survey tools designed respectively for nurses and UAPs. These tools were developed using a modified Delphi technique and a guide based on Burns et al. (2008) and Eysenbach (2004). They examine delirium knowledge, practice, collaboration, confidence, and the impact of the COVID-19 pandemic on practice relatively to delirium. Descriptive and inferential statistical analyses will be performed on this data. The qualitative phase will include focus groups and interviews with nurses and UAPs to explore topics from the survey tools more in-depth. Thematic analysis will be performed on the transcripts. Data from both phases will answer the two study aims.Discussion and Research Spin-offs: This study will be the first to report on the delirium care offered by UAPs. The survey tools developed can identify nurses’ and UAPs’ practices, and the barriers and facilitators to optimum nursing care for people with delirium.